Hierarchical Y Zeolite-Based Catalysts for VGO Cracking: Impact of Carbonaceous Species on Catalyst Acidity and Specific Surface Area - Fals, Jayson (2024)
The performance of catalysts prepared from hierarchical Y zeolites has been studied during the conversion of vacuum gas oil (VGO) into higher-value products. Two different catalysts have been studied: CatY.0.00 was obtained from the standard zeolite (Y-0.00-M: without alkaline treatment) and CatY.0.20 was prepared from the desilicated zeolite (Y-0-20-M: treated with 0.20 M NaOH). The cracking tests were carried out in a microactivity test (MAT) unit with a fixed-bed reactor at 550 ◦C in the 20–50 s reaction time range, with a catalyst mass of 3 g and a mass flow rate of VGO of 2.0 g/min. The products obtained were grouped according to their boiling point range in dry gas (DG), liquefied petroleum gas (LPG), naphtha, and coke. The results showed a greater conversion and selectivity to gasoline with the CatY.0.20 catalyst, along with improved quality (RON) of the C5–C12 cut. Conversely, the CatY.0.00 catalyst (obtained from the Y-0.00-M zeolite) showed greater selectivity to gases (DG and LPG), attributable to the electronic confinement effect within the microporous channels of the zeolite. The nature of coke has been studied using different analysis techniques and the impact on the catalysts by comparing the properties of the fresh and deactivated catalysts. The coke deposited on the catalyst surfaces was responsible for the loss of activity; however, the CatY.0.20 catalyst showed greater resistance to deactivation by coke, despite showing the highest selectivity. Given that the reaction occurs in the acid sites of the zeolite and not in the matrix, the increased degree of mesoporosity of the zeolite in the CatY.0.20 catalyst facilitated the outward diffusion of products from the zeolitic channels to the matrix, thereby preserving greater activity.